Fisheries resources in five Marine Protected Areas (MPAs) in Davao Oriental - Nanual, Bernadette J. (2014)
Fisheries profiling along with other key bio-resources and habitats was conducted in 2012 in five marine protected area (MPA) sites of the coastal corridor of Davao Oriental. This was done to generate information that will aid in the resource management efforts of the local government and mandated line agencies. Daily catch monitoring was made for four consecutive months and market information was examined through an enumerator stationed in each site. From the information gathered, it appears that all the monitored sites were predominantly engaged in municipal fishing and in capture fisheries. Both motorized and non-motorized boats were utilized. Net and hook-and-line gear were largely used. Specific fishing gear was employed to capture specific species. The fish catch and comprised of reef and offshore species but the latter contributes more to the catch. Catch was largely sold fresh and traded locally. Catch-per-unit-effort (CPUE) during the monitoring months (June – August) for all gear types was low that is less than 1 kg h-1 of fishing. Squid, needlefish and round-eyed scad dominated the catch. CPUE is highest in Brgy. San Ignacio, Manay for both hook and line and squid jigger. Gear combination increases the efficiency of fishing effort as can be confirmed from the higher CPUE.
Keywords: Mindanao studies; Fisheries